Digital Photography - Frederick, Shawn (Indianapolis, IN : Alpha, 2013)
Learn how to take pictures like the professionals. This introductory guide to digital photography explains the essential technical basics of every camera and lens. Illustrated step-by-step instructions teach you how to take pictures like the professionals. Master the timeless principles of great photography like balance, perspective and contrast. Plus, learn to do more with your photography skills through unique and creative projects by capturing portrait, panoramic and time-lapse images. You can finally switch your DSLR off auto mode and create beautiful, inspiring images!
Keywords: Photography -- Digital techniques